Antimicrobial resistance genes in marine bacteria and human uropathogenic Escherichia coli from a region of intensive aquaculture. Issue 5 (10th September 2015) - Tomova, Alexandra; Ivanova, Larisa; Buschmann, Alejandro H.; Rioseco, Maria Luisa; Kalsi, Rajinder K.; Godfrey, Henry P.; Cabello, Felipe C.
Summary Antimicrobials are heavily used in Chilean salmon aquaculture. We previously found significant differences in antimicrobial‐resistant bacteria between sediments from an aquaculture and a non‐aquaculture site. We now show that levels of antimicrobial resistance genes (ARG) are significantly higher in antimicrobial‐selected marine bacteria than in unselected bacteria from these sites. While ARG in tetracycline‐ and florfenicol‐selected bacteria from aquaculture and non‐aquaculture sites were equally frequent, there were significantly more plasmid‐mediated quinolone resistance genes per bacterium and significantly higher numbers of qnrB genes in quinolone‐selected bacteria from the aquaculture site. Quinolone‐resistant urinary Escherichia coli from patients in the Chilean aquacultural region were significantly enriched for qnrB (including a novel qnrB gene), qnrS, qnrA and aac(6′)‐1b, compared with isolates from New York City. Sequences of qnrA1, qnrB1 and qnrS1 in quinolone‐resistant Chilean E. coli and Chilean marine bacteria were identical, suggesting horizontal gene transfer between antimicrobial‐resistant marine bacteria and human pathogens.